Angle-dependent optical properties of advanced fenestration systems—Finding a right balance between model complexity and prediction error - Capperucci, Riccardo; Loonen, Roel C.G.M.; Hensen, Jan L.M.; Rosemann, Alexander L.P. (Building simulation, 2019)
Advanced glazing systems with special spectral characteristics or light redirecting behavior are commonly applied to improve building energy efficiency and indoor comfort conditions. The angle-dependent optical properties of such advanced windows can be markedly different from those of ordinary glass. To achieve accurate building performance predictions, it is necessary to represent the physical behavior of advanced window systems at a sufficiently high level of detail in building simulation programs. However, modelers should be aware that overly complex models are also undesirable, because they are costly to develop and input parameters are difficult to obtain. There is little guidance for simulation users to select an appropriate simulation strategy with respect to atypical glazing properties. This paper introduces a new approach for analyzing the influence of angle-dependent glazing properties, taking into account the effect of location and façade orientation. The potential of this method is demonstrated using an innovative switchable glazing system based on liquid crystals. A comparison between measured and derived transmission properties based on normal angle-of-incidence is presented. Results are presented for three European cities at different latitudes and for three different façade orientations. Using this new approach, simulation users can make informed decisions about appropriate modeling strategies for considering angular optical properties in building performance predictions.